INSOLVENCY RISK AND FINANCIAL RATIOS ANALYSIS IN PRIVATE EQUITY-OWNED COMPANIES: EVIDENCE FROM JOANN COMPANY. - Olimjonova Munisa Nuriddin qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This research paper examines the complex relationship between private equity (PE) investments and insolvency risk, particularly in the context of highly leveraged firms. With PE deal-making reaching approximately 2 trillion globally in 2024, an increase of 14% from the previous year, the economic impact of PE-backed firms is undeniable. However, these firms are also prone to insolvency risks due to their leveraged capital structures and rising bankruptcy filings, especially following the COVID-19 pandemic, highlight the insolvency risks associated with high debt levels inherent in PE acquisitions. The financial structure and metrics of PE-backed firms are investigated, focusing on the case of JOANN Company. While PE can offer substantial returns, it does have a need for monitoring of operations.